Analysis of Students' Creative Thinking Skills in Learning Hydrocarbons by Using Daily Life-Based Practicum Method - Kurniawati, Yenni; Handayani, Laras Dyaz; Ramadani, Dea; Sari, Nurhikmah (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
Creative thinking skill is a competence of the 21st century that is needed very much and needs to be increased by utilizing chemistry in life. This research aimed at analyzing student creative thinking skills in experimental and control groups and finding out the effect of the daily life-based practical work learning method on student creative thinking skills. This research was conducted in the eleventh grade at High School 1 Pekanbaru on the hydrocarbon lesson. The quasi-experimental method was used in this research with pretest-posttest and non-equivalent control group designs. The instruments used in this research were essay tests, observation, and interviews to find out student creative thinking. The result of data analysis showed differences: the creative thinking skill posttest mean score of the experimental group was 77.1, and the control group was 70. Based on the result of testing the hypothesis by using SPSS, sign. (2-tailed) 0.000 was lower than 0.05, so Ha was accepted and H0 was rejected. The highest difference among creative thinking skill indicators between experimental and control groups was elaboration, and the lowest difference was originality. We expect the results of this study to enhance students' creative thinking skills, given regular training.